Effect of isotretinoin treatment on sleep quality in acne vulgaris patients - Celik, Mehmet Semih; Celik, Candan; Cepik, Nagehan (Springer, 2025)
Isotretinoin is a systemic treatment agent used in patients with severe acne vulgaris. It has been reported to have side effects associated with depression, sleep apnea, and hypersomnia. There are some studies in the literature suggesting that isotretinoin may cause sleep disturbances. The aim of this study was to investigate whether sleep quality is affected in acne vulgaris patients receiving isotretinoin treatment. Fifty patients with acne vulgaris who were receiving isotretinoin treatment and who were referred to the dermatology polyclinic were included in the study. Two Pittsburgh Sleep Quality Index (PSQI) questionnaires, consisting of 7 components and 19 items, were administered to the patients, one during the treatment period and one before the treatment period. Scores ranged from 0 to 21, with scores of 5 and above indicating poor sleep quality. Before isotretinoin treatment, the average PSQI score of male patients was 11.5 +/- 4.95, while after treatment it was 18.0 +/- 6.69. In female patients, the average PSQI score before treatment was 9.50 +/- 4.81, During treatment, it was observed as 14.0 +/- 6.28. An increase in scores was observed in both sexes after isotretinoin. The change before and after treatment was considered significant (P < 0.001). In our study, we observed a negative effect of isotretinoin on sleep quality. Some experimental studies have shown that retinoic acids can affect the pathways in the brain that regulate sleep, but further research is needed in this area.
Keywords: Acne vulgaris; Isotretinoin; PSQI